SENTIMENT OF SOCIAL MEDIA USAGE, INFLUENCER MARKETING AND CONTENT MARKETING ON COMPETITIVE ADVANTAGE AND DIGITAL MARKETING IN BUSINESSES IN BATAM CITY - Wibowo, Edwin Agung; Anggraini, Dini (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2025)
The focus and purpose of this research will certainly analyze the role of social media, influencer marketing and content marketing on the business success of Micro, Small and Medium Enterprises in Batam City. The sample determination of this study refers to the Maximum Likelihood Estimation (MLE) ranging from 100-200 samples. So, the study determined a sampling of 150 MSME business people spread across Batam City by determining the sample using purposive sampling technique with predetermined criteria. The results of hypothesis testing found that social media marketing variables have no impact on competitive advantage, influencer marketing variables have an impact on competitive advantage, content marketing variables have an impact on competitive advantage, influencer marketing variables have an impact on digital marketing, content marketing variables have no impact on digital marketing and competitive advantage variables have an impact on digital marketing.